A Rare Case of Intermuscular Lipoma in the Neck - Rees, Charles Malcolm; Gasteratos, K; Atta, Ahmed (RA Journal of Applied Research, 2018)
Deep seated lipomas are a rare entity in the literature with the intermuscular lipomas accounting for less than 2% of all benign lipomas. This is a case report of a 35 years old male which presented to clinic with a six month history of a left sided neck lump located in the left posterior cervical triangle. Intermuscular lipoma was confirmed using ultrasound and measured 67x42x12mm. In view of its size the patient underwent surgical excision under general anaesthetic. This case study details the importance of preoperative assessment of neck lumps, the surgical techniques used and possible complications of such procedures.